Beck depression inventory, second edition, Czech version: demographic correlates, factor structure and comparison with foreign data - Ciharova, Marketa; Cígler, Hynek; Dostálová, Veronika; Šivicová, Gabriela; Bezdicek, Ondrej (International journal of psychiatry in clinical practice, 2020)
OBJECTIVE: We aimed to examine whether demographic characteristics (i.e., sex, age and education) correlate with total scores of the Czech version of the Beck Depression Inventory (BDI-II), understand the factorial structure of this scale, compare our results with findings of studies conducted in other countries and provide preliminary normative data for use in clinical practice. METHODS: Data of 450 participants were analysed using correlation analysis, non-parametric tests and confirmatory factor analysis (CFA). RESULTS: Women, and participants with lower education, tended to score higher than men, and participants with higher education. There was no significant relationship between age and total scores. CFA confirmed two factors: cognitive-affective and somatic. Czech participants scored lower than participants in other studies. Preliminary normative data are presented in the form of percentile values for the whole sample and stratified according to gender and education level. CONCLUSIONS: We recommend the usage of the BDI-II total score while taking into account also the cognitive-affective and somatic factor subscores. The comparison of our results with other foreign findings shows the need for the development of locally specific normative values for self-reported depression scales. KEY POINTS Women scored higher in the BDI-II than men. Participants with lower education scored higher in the BDI-II than participants with higher education. CFA confirmed two factors: cognitive-affective and somatic. Preliminary normative data for the Czech version of the BDI-II are stratified according to gender and education.
Keywords: Sex Factors; Humans; lidé středního věku; factorial structure; Female; dospělí; faktorová analýza statistická; Psychiatric Status Rating Scales; lidé; Factor Analysis, Statistical; sexuální faktory; Adult; ženské pohlaví; Depressive Disorder; psychiatrické posuzovací škály; Male; depresivní poruchy; Middle Aged; confirmatory factor analysis; Psychometrics; Czech Republic; stupeň vzdělání; Depression; normative data; Beck Depression Inventory; Česká republika; mužské pohlaví; deprese; psychometrie; Educational Status